Presidential Address - The South African Coal Industry: Current Position And Future Challenges - R. P. Mohring (The Southern African Institute of Mining and Metallurgy, 1997)
The South African Coal Industry had its beginnings in the Eastern Cape in 1859 when coal was mined to satisfy the fledgling settlements in the Eastern Cape. The growth in the industry was relatively slow up to the early 1970s when, firstly, the export business was expanded coupled with a major increase in the quantity of coal converted to liquid fuels and utilized for power generation. To meet this increased demand the industry developed many new operations employing the latest mining technology and systems. Coal production in South Africa reached 204 million tons in 1996 and revenue from exports reached R8 billion making it the second-largest foreign exchange earner after gold. In his address Rick P. Mohring describes the role coal plays in the international energy scene and outlines South Africa?s position as a producer and consumer of coal, and the challenges facing the industry. A wide range of steam-coals are produced to satisfy both the local market (power generation, coal conversion and the metallurgical industry) and the export steam-coal market. South Africa is in a unique position regarding the export market as it is still a relatively low-cost producer and is geographically well-placed to play in both the European and Far East markets. There are, however, a number of challenges facing the industry. To retain our competitiveness in the international market, ways of minimizing the cost pressures caused by high-cost inflation, increased environmental protection obligations and a decreasing quality resource base need to be sought. Locally the coal mining industry has a major role to play in Eskom?s goal of reducing the real cost of electricity by 15% in the next three years. Safety and health, productivity and the adaptation of the latest technology are issues being addressed by the industry to maintain its dominant position within the South African economy.